Optimizing diesel engine performance and emissions with mahua biodiesel blends using taguchi methodology - G. Praveen Kumar Yadav; Din Bandhu; Suman Chatterjee; Prashant Kumar Gangwar (PLoS ONE, 2025)
This study investigates how adjusting operational parameters influences the performance and emission characteristics of a diesel engine operating on a blend of traditional diesel fuel and mahua biodiesel. The biodiesel was obtained using the transesterification method, and fuel blends were formulated with diesel proportions ranging from 80% to 100% and biodiesel content from 0% to 20%. Key engine parameters such as engine load (20 –100%), mahua biodiesel blend (0 –20%), and engine speed (1300 –1450 rpm) were varied systematically during the experiments, while the compression ratio was held constant at 18:1. The aim was to determine the most effective combination of settings to enhance combustion efficiency and reduce harmful exhaust emissions. The findings demonstrated a modest yet meaningful improvement in engine efficiency, with gains of approximately 2–3%. While seemingly incremental, this enhancement becomes significant when coupled with concurrent reductions in harmful emissions, aligning with global efforts to transition toward sustainable fuel alternatives. The optimized biodiesel blends not only improved fuel utilization but also advanced environmental objectives by mitigating pollutant emissions, underscoring their dual role in enhancing performance and ecological sustainability. The outcomes of this study support the potential of mahua biodiesel as a viable and eco-friendly supplement to petroleum diesel. Overall, the results contribute meaningful data toward improving diesel engine performance while reducing environmental pollution.